ART IN ELEMENTARY EDUCATION: CURRICULAR GUIDELINES, CHALLENGES, AND PEDAGOGICAL POSSIBILITIES - dos Santos, Marta Rosangela Alves; Pinheiro, Danielle Ventura de Lima (Seven Editora, 2026)
This article is the result of a dissertation defended in a Postgraduate Program in Education that aimed to analyze Art as an essential field of knowledge in the integral formation of individuals, even though, historically, it has occupied a secondary position in school curricula. This study analyzes the curricular guidelines for the subject of Art in Elementary Education, identifying pedagogical challenges and possibilities. The investigation was based on bibliographic research, document analysis, and a review of academic literature (2013-2023). As a theoretical basis, the studies of authors Ana Mae Barbosa, Ferraz & Fusari, Paulo Freire Pérez-Gómez, Imbernón, among others, were consulted, in addition to normative documents (LDB, PCNs, BNCC). The results indicate a shortage of specialist teachers, weaknesses in infrastructure, and a predominance of traditional methodologies. However, they also point to innovative experiences that value cultural diversity and student protagonism. It is concluded that valuing art in the curriculum, combined with consistent public policies and ongoing teacher training, is a necessary condition for a critical, creative, and civic education.